Young Adult Perception of Fermented Durian (Tempoyak) in Lampung Province, Indonesia - Lasuardi Permana; Hesti Ayuningtyas Pangastuti; Amalia Wahyuningtyas (Journal of Science and Applicative Technology, 2021)
Tempoyak is fermented food made from durian (Durio zibethinus) pulp. This product is popular traditional food in Indonesia and Malaysia. To ensure the current position of tempoyak and its dishes in young generation, this research was conducted to obtain young adult perception about tempoyak as traditional food in Lampung, and also discover about its potential for innovation. Method for investigate the response of young adults to tempoyak as traditional food was using direct questionnaire survey through google form. A total of 115 respondents have participated in the survey, consisted of 43 men and 72 women. The result showed that all of the respondent were familiar with tempoyak, but only three-quarter of them had ever taste of its products. Half of the respondent were preferred intermediate acidity level of tempoyak, and the rest of them preferred tempoyak with low acidity level and sweet taste. More than 95% of respondents agreed that tempoyak needs innovation to be better known in public. The innovation needed were product form (55%), packaging innovation (21%), instant product innovation (18%), others (5%), and marketing strategy (1%).